2020
DOI: 10.1109/access.2020.3034770
|View full text |Cite
|
Sign up to set email alerts
|

An Easy-to-Use Multi-Source Recording and Synchronization Software for Experimental Trials

Abstract: A typical routine in many scientific studies consists of recording data from devices and identifying which segment of data corresponds with an experimental interval. However, many current applications have been designed to obtain and save data from one single device, and synchronizing data with the markers that delimit the test phases can be difficult. To address this issue, we have developed LSRec, which is based on Lab-Streaming Layer, a C++ library that allows data synchronization. LSRec is an easy-to-use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…As computation resources are more limited on wearables, some authors have suggested using external and more powerful devices to process the signals [82,83]. In our case, we used the "edge computing" concept implemented on a Raspberry Pi 4 B with Raspberry Pi OS and an ad hoc application called LSL Recorder [84], for data synchronization and storage, based on Lab-Streaming Layer (LSL). This software is an easy-to-use, open-source, multi-platform, recording system developed on Java that can save data from several devices at the same time, while maintaining synchronization with the experimental phase markers based on LSL library, such that LSL is "a system for the unified collection of measurement time series in research experiments that handles both the networking, time-synchronization, (near-) real-time access as well as optionally the centralized collection, viewing and disk recording of the data" [85] (Figure 6).…”
Section: Software 221 Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…As computation resources are more limited on wearables, some authors have suggested using external and more powerful devices to process the signals [82,83]. In our case, we used the "edge computing" concept implemented on a Raspberry Pi 4 B with Raspberry Pi OS and an ad hoc application called LSL Recorder [84], for data synchronization and storage, based on Lab-Streaming Layer (LSL). This software is an easy-to-use, open-source, multi-platform, recording system developed on Java that can save data from several devices at the same time, while maintaining synchronization with the experimental phase markers based on LSL library, such that LSL is "a system for the unified collection of measurement time series in research experiments that handles both the networking, time-synchronization, (near-) real-time access as well as optionally the centralized collection, viewing and disk recording of the data" [85] (Figure 6).…”
Section: Software 221 Communicationmentioning
confidence: 99%
“…LSL is very useful for keeping the synchronization and data coherence in a simple way. The data streams are recorded by LSL Recorder [84], a software application that can be run in any computer connected to the same LAN as the edge computer, or on the edge computer itself.…”
Section: Data Synchronizationmentioning
confidence: 99%
“…An additional Java application registered, recorded, and synchronized all the information generated during the experiment [ 49 ]: the NM raw data, cursor coordinates, FSM state, blinks, and attention level. Hence, the whole experiment can be reproduced offline for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For such cases, Independent Component Analysis (ICA) will be utilized, as it is an efficient algorithm for source separation and artifact removal in EEG signals. The data will be recorded in a synchronized manner using a software application (Figure 3) designed for this purpose [34]. The software utilizes the LabStreaming Layer library.…”
mentioning
confidence: 99%